THE USEFULNESS OF SPIRITUAL AND EDUCATIONAL REFORMS IN BUILDING A CORRUPTION-FREE SOCIETY (Scientific journal of the Fergana State University, 2023)
This article discusses the importance, relevance and effectiveness of spiritual and educational work in the process of transforming New Uzbekistan into a country free of corruption. The national and spiritual bases of the fight against corruption and the essence of the ongoing reforms in the country are also highlighted.